The Effectiveness of Compassion-Based Spouse-Treating Education on the Improvement of Family Relationships and Forgiveness in Married Deaf and Hard of Hearing Men in Isfahan - karimnezhad Isfahani, Reyhaneh; Mardani, Farzaneh (KMAN Counseling & Psychology Nexus, 2023)
The present study aimed to evaluate the effectiveness of compassion-based spouse-treating education on improving family relationships and forgiveness among married deaf and hard of hearing men in Isfahan. This research was a quasi-experimental study with a pre-test, post-test, and follow-up design, or control group. The sample consisted of 30 volunteer men from the deaf or hard of hearing population in Isfahan, who were non-randomly (conveniently) assigned to either the experimental or control groups, with the control group being on a waiting list. The experimental group received an educational package over 8 sessions of 120 minutes each. The research tools were the Olson and Barnes Family Relationships Questionnaire (2004) and the Thompson et al. Forgiveness Questionnaire (2005). Both groups were assessed at three stages: pre-test, post-test, and follow-up. Descriptive and inferential statistics (repeated measures analysis of variance) were used for data analysis (p < 0.01). The results showed that compassion-based spouse-treating education significantly improved family relationships and forgiveness. According to the findings of this research, it can be said that compassion-based spouse-treating education is an appropriate method for improving marital relationships and increasing forgiveness among deaf men.